Acne Vulgaris Treated with Individual Homoeopathic Medicine: A Case Study (Homoeopathy for All, 2022)
The most prevalent age for acne,  an inflammatory disorder of the  pilosebaceous units, is adolescence.  Open (black) and closed (white)  comedones, inflammatory papules,  pustules, nodules, and cysts are  the typical lesions, which may  result in scarring and pigmentary  alterations. Acne vulgaris is a  frequent diagnosis made by a  physician for eruptions occurring  on the face of teenagers described  as “PIMPLE” by a layperson.  Homoeopathy treats Acne vulgaris  either on the basis of constitutional  or therapeutics and achieves  great success. Here presenting  a case of Miss Xx, age 21 years  old female came to OPD with  complaints of acne vulgaris cured  by constitutional homoeopathic  medicine.
Keywords: Acne vulgaris; Constitutional homoeopathic medicine; Natrium muriaticum; Synthesis repertory radar 10